Elemental diet induces alterations of the gut microbial community in mice - Andoh, Akira (J Clin Biochem Nutr, 2019)
The aim of the present study was to investigate elemental diet (ED)-induced alteration of the fecal and mucosal microbiome in mice. The control group was fed a normal chow and the ED group was fed normal chow containing 50% w/w Elental(®) (EA Pharma, Tokyo, Japan) for 28 days. Fecal and mucosal microbiome were analyzed using 16S rRNA gene sequencing. In the fecal samples, the observed species, an index for microbial richness, was significantly decreased in the ED group. Principal coordinate analysis revealed that there were significant compositional differences between the control and ED groups (PERMANOVA p = 0.0007 for unweighted and p = 0.002 for weighted UniFrac distance, respectively). In contrast, there was no significant difference in the overall structure of mucosal microbiome between the control and ED groups. In the fecal samples, abundance of the genera Adlercreutzia, Akkermansia, Streptococcus, Helicobacter, Coprobacillus and Coprococcus was significantly reduced in the ED group compared to the control group. Abundance of the genera Lactobacillus and Staphylococcus was significantly increased in the ED group. In a functional analysis using PICRUSt software, ED altered various pathways involved in amino acid metabolism of the gut microbiome. In conclusion, ED caused a reduction in bacterial diversity and altered metabolic functions.